Peningkatan Kemampuan Penalaran Matematis Pada Mata Kuliah Geometri Transformasi Berbantuan Software GeoGebra - Mochammad Rasyid Ridha; Agung Cahya Gumilar; Estiyan Dwipriyoko (Fakultas Teknik Universitas Langlangbuana, 2020)
This paper notes a finding from research on GeoGebra-assisted learning. This study used a pretest-postest design with a control group. The purpose of this study was to analyze students' mathematical reasoning abilities in the Transformation Geometry course. There are 24 research subjects. They are the fourth semester students of the mathematics education study program. The instruments used were student tests and non-tests. Based on the results of the data analysis, the researcher found: there was a significant increase in mathematical reasoning abilities and the disposition of students who were given learning using GeoGebra software. Then, the improvement was reported to be better than the conventional class in all categories. Other results also show a relationship between mathematical reasoning abilities and student dispositions in the medium category.